Maintaining the efficacy of warm-up activities in EFL classrooms: An exploratory action research - Savaş, Hasan (My University, 2016)
The current study is an Exploratory Action Research and was carried out for the purpose of enhancing the efficacy of warm-up activities used in EFL classrooms. The participants of the study were A2 (pre-intermediate) level English preparatory students at a foundation university in Turkey, and their ages ranged from 18 to 21. The data were gathered through two different questionnaires in the form of students' reports in order to provide answers to two research questions. First, an Exploratory Practice (EP) was carried out with the participation of 32 students from two skill-based listening and speaking classes by using the first questionnaire as the data collection tool. The aim was to understand what warm-up activities/practices meant to students and to investigate students' perceptions on the use of warm-up activities as tools to increase participation in classes. Following the findings of EP, an Action Research (AR) was carried out in one of the classes with the participation of 21 students for a four-weeks period. The AR study was the implementation of the emerged themes from the EP in the form of redesigned warm-up activities. Following the classroom implementations, the second data collection tool, which was the second questionnaire, was distributed to the students. The findings of the second questionnaire provided the reflections of the students on the AR study. The collected data were content analyzed and the teacher researcher provided reflections on the overall process.

Mevcut çalışma bir keşif ve eylem araştırmasıdır ve İngiliz dili eğitimi sınıflarında uygulanan ön- hazırlık faaliyetlerinin yeterliliklerini geliştirmek amacı ile uygulanmıştır. Çalışmanın katılımcıları Türkiye'de bir vakıf üniversitesinde İngilizce hazırlık okulu'nda öğrenim gören A2 (alt orta seviye) kuru öğrencileridir. Katılımcıların yaşları 18 ile 21 arası değişmektedir. Çalışmada veri iki adet araştırma sorusuna cevap aramak için öğrenci raporları şeklinde iki farklı anket formu kullanılarak toplanmıştır. Ilk önce birinci data toplama aracı olarak kullanılan anket formu 32 öğrencinin katılımıyla keşif araştırması şeklinde uygulanmıştır. Amaç ön-hazırlık faaliyetlerinin öğrenciler için ne anlama geldiğini anlamak ve sınıf içi katılımı artırmak için kullanımlarında öğrencilerin algılarını araştırmaktır. Keşif araştırmasının bulguları üzerine 21 öğrencinin katılımı ile bir sınıfta eylem araştırması dört hafta boyunca uygulanmıştır. Eylem araştırması keşif araştırması sonucu ortaya çıkan temalar üzerine dizayn edilmiş ön-hazırlık faaliyetlerinin sınıf içinde uygulanması şeklinde yürütülmüştür. Sınıf içi uygulamaları sonrasında ikinci data toplama aracı olarak kullanılan anket formu öğrencilere dağıtılmıştır ve sonucunda öğrencilerin eylem araştırması sonrasındaki algıları araştırılmıştır. Toplanan tüm veriler içerik analiz edilmiştir ve öğretmen- araştırmacı tüm süreç ve çalışma çıktıları üzerine değerlendirmelerini yapmıştır.
İngiliz dili eğitimi sınıflarında ön-hazırlık faaliyetlerinin yeterliliklerinin sağlanması: Keşif ve eylem araştırması
Keywords: Action Research; Exploratory Practice; EFL Classrooms; Teacher’s Self Development; Keşif Araştırması; Eylem Araştırması; İngiliz Dili Eğitimi; Öğretmen Gelişimi